2020
DOI: 10.15421/112030
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and geographical structure of inbound tourism in political transit countries: case of Ukraine

Abstract: Ukraine is an important component of the world market for inbound tourism. From the beginning of the twentieth century in some years it was included in the list of the world leading tourist countries in terms of international tourist arrivals. To study modern trends in the development of inbound tourism in Ukraine, during the period of independence, the concept of tourist transit, developed by D. Hill, is applied. It is а part of the wider concept of political and economic transit, well known in the social sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…To determine the level of hotel development of tourism regions of Ukraine, based on quantitative indicators of tourist flows, the dynamics of tourist arrivals, revenues from services, the state of material and technical base, i.e. tourist infrastructure were used methods of statistical trend analysis (Chattopadhyay, & Mitra, 2019;Lozynskyy, & Kushniruk, 2020). The analysis of time series is to establish patterns of changes in the levels of the studied indicator over time, to identify the main trend of the phenomenon -a certain direction of change: the tendency to increase, stability or decrease the levels of the phenomenon.…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…To determine the level of hotel development of tourism regions of Ukraine, based on quantitative indicators of tourist flows, the dynamics of tourist arrivals, revenues from services, the state of material and technical base, i.e. tourist infrastructure were used methods of statistical trend analysis (Chattopadhyay, & Mitra, 2019;Lozynskyy, & Kushniruk, 2020). The analysis of time series is to establish patterns of changes in the levels of the studied indicator over time, to identify the main trend of the phenomenon -a certain direction of change: the tendency to increase, stability or decrease the levels of the phenomenon.…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…These resorts are now among the largest in Central and Eastern Europe in terms of annual number of visitors, number of accommodation facilities, the number and length of ski slopes. The tourism industry is capable of rapid recovery after economic crises (Lozynskyy & Kushniruk, 2020).…”
Section: Mountain Villagesmentioning
confidence: 99%
“…These are the main factors affecting the economic level of a tourist destination country. Additionally, recent studies have shown that country branding is important for inbound tourism (Lozynskyy and Kushniruk, 2020; Papp-Váry, 2019). To attract more international visitors, many countries, such as the United States (U.S.) (Zavattaro and Fay, 2019), New Zealand (Lodge, 2002; Vatsa, 2020), Spain (Fiona, 2002; Vicens-Colom et al, 2021), Finland (Aho, 2014; Vento et al, 2020), and Scotland (Melis and Chambers, 2021; Olins, 2000), not only promote their natural attractions but also distinguish their destinations through branding strategies that establish their unique positions.…”
Section: Introductionmentioning
confidence: 99%